SP0009 Primary Central Nervous System Vasculitis. (9th June 2015) - Salvarani, C.
Abstract : Primary CNS vasculitis is an uncommon disorder of unknown cause that is restricted to brain and spinal cord. The median age of onset is 50 years. The neurological manifestations are diverse, but generally consist of headache, altered cognition, focal weakness, or stroke. Serological markers of inflammation are usually normal. Cerebrospinal fluid is abnormal in about 80-90% of patients. Diagnosis is unlikely in the presence of a normal MRI of the brain. Biopsy of CNS tissue showing vasculitis is the only definitive test; however, angiography has often been used for diagnosis even though it has only moderate sensitivity and specificity. The size of the affected vessels varies and determines outcome and response to treatment. Early recognition is important because treatment with corticosteroids with or without cytotoxic drugs can often prevent serious outcomes. The differential diagnosis includes reversible cerebral vasoconstriction syndromes and secondary cerebral vasculitis. Disclosure of Interest: None declared